(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The study evaluated anxiety and life quality (LQ) of undergraduate freshman students from health Science courses of a public university (study 1). In light of the results, a group intervention study was performed (study 2). This intervention consisted of eight sessions, of 90 min each. In two of the sessions, a biofeedback training device, that monitors the variability of the heart rate, was employed. The subjects were evaluated before and after the intervention by the State-Trace Anxiety Inventory and by the Medical Outcomes Study 36 – Item short form health survey. Levels of anxiety were higher and LQ aspects were lower in female students, independently of the undergraduate course. Men from the course of Physical Education showed higher scores in diferente domains that measured LQ. The intervention significantly reduced levels of anxiety and improved mental health. These data reaffirm the importance of the development of psychotherapeutic programs by the university.